FAKTOR YANG MEMPENGARUHI NILAI JUAL PADA PERUMAHAN TIPE SEDERHANA SEHAT DI KAWASAN AGLOMERASI PERKOTAAN YOGYAKARTA - Nuraeni, Nuraeni; Khasanah, Uswatun (Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
The population density in the city of Yogyakarta has created the Yogyakarta Urban Agglomeration (Aglomerasi Perkotaan Yogyakarta/APY) area consisting of Bantul Regency and Sle-man Regency which has an impact on the increasing population and growth rate of housing needs in the APY area. This study aims to determine the factors that most influence the selling value of land and buildings in simple type housing and to determine the level of significance and correlation between the factors that affect the selling value of land and buildings in simple type housing in the APY area. Data collection was carried out by distributing questionnaires to residential residents in the APY area of Sleman Regency as respondents by sampling. Data processing was carried out by a method in the form of the Relative Rank Index (RRI) value. The results showed that the factors that most influence the selling value of land and buildings in simple type housing in the APY area are 1) Public Transportation, 2) Distance to Shopping Centers, 3) Distance to Workplace, 4) Distance to City Center, 5) Distance to Educational Facilities.Keywords: Yogyakarta Urban Agglomeration, housing, sale valueJEL Classification:H4,O1